KAP1-Paupar lncRNA chromatin regulatory complex controls subventricular zone neurogenesis - Alammari, F (2019)
Neurogenesis continues postnatally in two major neural stem cell (NSC) niches, the subventricular zone (SVZ) and dentate gyrus of the hippocampus. NSCs in the SVZ exhibit some biological features of glia, especially astrocytes. However, it is still not clear how NSCs in the SVZ can maintain stem cell self-renewal properties and the potential to generate transit amplifying progenitor cells (TAPs) that give rise to neuroblasts. Neuroblasts migrate through the rostral migratory stream (RMS) to the olfactory bulbs where they differentiate into neurons. In this project, I investigated the function and mode of action of a new KAP1-lncRNA chromatin regulatory complex in the control of postnatal and adult neural stem cell (NSC) self-renewal and neurogenesis.